Assess the Performance of Secondary School Principals in Jeddah to Achieve Saudi Arabia’s Vision Targets Accordance with the Hellinger’s Measure From Teachers View points - Fadhil, Rogaiae Faisal; ALthabiani, Abrar Housain; Alharbi, Hayat Mohammad Saad (Journal of Educational and Psychological Sciences, 2025)
The study aimed to evaluate the performance of secondary school principals in Jeddah to achieve the targets of Saudi Vision 2030, based on teachers’ perspectives and using the Hallinger scale. A descriptive methodology was employed, utilizing a questionnaire consisting of (60) items distributed across seven domains. The study population included 5,456 teachers, from which a simple random sample of (392) teachers was selected. The results showed that the overall mean score for performance evaluation was (4.23) indicating a very high level. The mean scores for the first five domains ranged between (4.13) and (4.36) all at a very high level. The domain “Improving the school’s performance rating” ranked first with a mean of (4.36), followed by “School goals” (4.25), “Monitoring school affairs” (4.24), “Curriculum supervision” (4.24), and “Student achievement and motivation” (4.23). The remaining two domains, “Professional development of teachers” (4.19) and “Community partnerships” (4.13), ranked last but were still rated highly. The study recommended strengthening community partnership programs between educational leaders and the local community, establishing clear standards for teachers’ professional development to serve as a basis for performance evaluation and promotion systems, and adopting the Hallinger scale as a scientific framework for evaluating school leadership performance.